The problems of principles of study the graphical programs in training specialists of design profession in higher educational exublishments (Pedagogy of Higher and Secondary Education, 2006)
In article opened the problems concerned with expedition new discipline computer drawing in higher educational establishments in training specialists of design profession.
Keywords: compuser-based technology; drawing soft; compehensive approach